Device Characterization of 0.21 Î¼m CMOS Device - Foo, Lim Teck; Ahmad, Ibrahim; Sulong, Muhammad Suhaimi (Journal of Science and Technology, 2009)
The objective of this study was ot measure the electrical characteristics, observe the structure and characterize the material of 0.21μm CMOS devices. The material characterization of the 0.21μm CMOS devices were carried out using FIB milling technique, SEM surface morphology and EDX Analysis. The CVIV tester was used for electrical characterization of the device. All the IDVD and IDVG graphs obtained are similar to the standard graph. There are two ways to calculate the devices VTH manual calculation method and auto calcualtion method. Calculation of the VTH by using the manual calcuation method was found to be more accurate than the auto calcuation method. The VTH value for NMOS and PMOS obtained from this study is 0.398393 AND -0.715700. Both these values are compared with the standard VTH value from Silterra, where this calculation involved polynomial regression technique in MATLAB. It is found that, the tested PMOS devices are practical but the tested NMOS devices are not. The materials used to fabricate this device has been obtained and shown. The electrical and material characteristics of the 0.21μm CMOS devices are successfully characterized by using the above methods.